Synthesis of Novel Polyazinyl-Substituted Triazolopyridines from [1,2,3]Triazolo[1,5-a]pyridines - Adam, Rosa; Abarca, Belén; Ballesteros, Rafael (Synthesis, 2017)
A series of 7-azinyl-substituted triazolopyridines and 3-(6-azinyl-substituted 2-pyridyl)triazolopyridines were synthesized by addition of the corresponding 3-substituted 7-lithiotriazolopyridine to pyrimidine, pyrazine, pyridazine, and 1,3,5-triazine respectively, followed by hydrolysis and oxidation.
Keywords: triazolopyridines; diazines; triazines; lithiation reactions; polynitrogenated ligands